Features of aggression regarding homeless children - Sandu, Mihaela Luminita; Rus, Mihaela; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2021)
Starting from the fact that man is a social being and the reality that teen, street child, living among people belonging to the same social environment, acting through a set of ways the environment, relationships with others, he must form a proper attitude and prosocial behavior. Respect individuality, training and development in line with its own development guidelines are necessary conditions in the educational process. Street children are those who are deprived of all monitoring and control, those who are exposed to overcrowding, hunger, cold and different risks. Due to their physical and emotional fragility, they are among the first victims of aggression. Their adaptation to life on the road conditions allow them to survive in a context where no professional skills, no money, no shelter and are likely to be exploited, physically and sexually abused. Survival in the street becomes possible through group membership, learn various skills in which they are intended to provide a form of income, their improvised shelters, most often in the channels and / or staircase, he organized a program day. They learn how to conduct profitable activities, limit their definition as legitimate and how to avoid being arrested or convicted, usually know that nothing happens to be minors.